Synergy Between Government And Humanitarian Agencies In Implementing Post-Disasters Relocation: The Buddha Tzu Chi Permanent Housing In Palu City - Reyva Alviona Fernanda Priskilla Priskilla; Sulfitri Husain; Muhammad Arief; Rusmawaty Bte Rusdin; Sisrilnaldi (POLITICO, 2026)
The natural disaster that struck Palu City in 2018 caused significant social and economic impacts, including the loss of homes for thousands of residents. In response, the Buddha Tzu Chi Foundation built permanent housing for the affected victims. This relocation brought about various changes in the community's lives, including social, economic, and psychological aspects. Therefore, this study aims to analyze the impact of relocation on the changing conditions of residents living in Buddha Tzu Chi's permanent housing. The research focuses on socio-economic adaptation, access to public services, and the sustainability of community well-being after the relocation. This study uses a quantitative approach with a survey method of residents who have settled in Buddha Tzu Chi's permanent housing. Data were collected through questionnaires that measured aspects of social, economic, and psychological well-being before and after the relocation. Descriptive and inferential statistical analyses will be used to examine the relationship between relocation and changes in community conditions. The research stages include primary and secondary data collection, data processing and analysis, and interpretation of the results to provide an accurate picture of the impact of relocation. The research findings are expected to contribute to academics, policy practitioners, and humanitarian organizations in understanding and managing the impact of post-disaster relocation.